Evaluation of Selection Criteria of Clinicians in the Treatment of Osteoporosis, OSTREQ Research in Türkiye - Emir Gökhan Kahraman; Barış Önder Pamuk; Servet Akar; Aliye Tosun (Türk Osteoporoz Dergisi)
Objective: This study aims to adapt the OSTREQ questionnaire, developed by Makras et al., into Turkish to assess the factors that clinicians take into consideration when planning osteoporosis treatment, as clinicians take many factors into consideration when making their decisions due to various treatment options. Materials and Methods: The Turkish version of the OSTREQ questionnaire, comprising 17 questions and an 8-section format, used a 5-point Likert scale. From April 2018 to November 2019, the survey was conducted with 188 clinicians in rheumatology, physical therapy, rehabilitation, endocrinology, and metabolic diseases. After excluding 18 duplicate responses, data from 170 clinicians were analyzed. Results: Participants included 21.8% endocrinologists, 28.8% rheumatologists, and 49.4% physical therapy and rehabilitation specialists. Factor analysis showed item loadings between 0.33 and 0.92, exceeding the 0.32 threshold. The overall Cronbach’s alpha was 0.855, indicating high internal consistency. There were no significant differences among specialties in subscales like “disease severity and treatment efficacy”. However, rheumatologists scored significantly higher than endocrinologists on “health system and cost” (p=0.034). Conclusion: The Turkish OSTREQ questionnaire is a valid, reliable tool for evaluating factors in osteoporosis treatment decisions. With minimal modification, it can assess clinicians’ views on specific anti-osteoporotic agents, aiding healthcare and pharmaceutical stakeholders.